PERLINDUNGAN HAK KONSUMEN SEBAGAI BAGIAN DARI PERLINDUNGAN HAK ASASI MANUSIA - Ari Purwadi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
Consumer’s dispute involves 2 parties, consumer and producer or distributor. The subject of the dispute is the violation of consumers’ right, while the Consumer Protection Law (UUPK) extends the comprehension of the protective parties in the transaction. Considering characteristic of consumer’s dispute, the National Committee of Human Rights should involve to conduct the controlling function. Consumer’s right is a kind of positive right that is included as basic rights (i.e. human rights). Based on human rights study, consumer’s right is also included in the economic, social and culture rights.